2011
DOI: 10.1016/j.jtcvs.2010.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Role of conservative management in traumatic aortic injury: Comparison of long-term results of conservative, surgical, and endovascular treatment

Abstract: The advent of thoracic aortic endografting has enabled a revolution in the management of acute traumatic aortic injury in patients with multisystem trauma with a low in-hospital morbimortality. Nonoperative management may be only a therapeutic option with acceptable survival in carefully selected patients. The natural history of these patients has revealed a marked trend of late aortic-related complications developing, which may justify an endovascular repair even in some low-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 26 publications
3
30
1
1
Order By: Relevance
“…Injury can occur along the entire length of the aorta, essentially from the ascending aorta to the iliac bifurcation, although the injury typically occurs areas of aortic tethering, notably the aortic isthmus. There exist three major theories that account for the mechanism of injury (it is likely that they collectively explain the mechanism and not one explanation is correct by itself): primarily, the aortic isthmus is a transition zone from the unfixed aortic arch to the fixed descending aortathis area is predisposed to go in opposite vectors during a rapid deceleration and can lead to a tear in the intima [10,11]; secondly, weaker tensile strength exists in the tissue of the aortic isthmus making it intrinsically more vulnerable to injury [10,12]; and thirdly, a compression point between the anterior chest's osseous structures and the spine acts in a way that pinches the aorta during a deceleration trauma [10,13]. Porcine models identified an initial tear in the intima and media first from these forces causing a dissection [14].…”
Section: Introductionmentioning
confidence: 99%
“…Injury can occur along the entire length of the aorta, essentially from the ascending aorta to the iliac bifurcation, although the injury typically occurs areas of aortic tethering, notably the aortic isthmus. There exist three major theories that account for the mechanism of injury (it is likely that they collectively explain the mechanism and not one explanation is correct by itself): primarily, the aortic isthmus is a transition zone from the unfixed aortic arch to the fixed descending aortathis area is predisposed to go in opposite vectors during a rapid deceleration and can lead to a tear in the intima [10,11]; secondly, weaker tensile strength exists in the tissue of the aortic isthmus making it intrinsically more vulnerable to injury [10,12]; and thirdly, a compression point between the anterior chest's osseous structures and the spine acts in a way that pinches the aorta during a deceleration trauma [10,13]. Porcine models identified an initial tear in the intima and media first from these forces causing a dissection [14].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, haemodynamically unstable patients may have two distinct pathophysiological processes—patients with full-thickness tear of the aorta and patients with other sources of clinically significant haemorrhage from associated injuries to the chest or abdomen 26. It is the latter group that is more likely to be seen in hospital, though patients may present without haemodynamic instability at all if major associated injuries are not present.…”
Section: Discussionmentioning
confidence: 99%
“…The in-hospital mortality rate was only 8% in this study. Mosquera et al (34) studied 66 patients with acute thoracic aortic pathology and reported higher short and long-term survival rates in the endovascular treatment group than in the surgical and conservative groups.…”
Section: Discussionmentioning
confidence: 99%